Development of Sustainability and Ethics Related Metrics to Guide Market Shaping Efforts by Microbusinesses - Harichand, Simran (2022)
Sustainability agendas have been around for a long time. As concerns about climate change rose, so did the need to reduce the carbon footprint of industries. Sustainability then grew into more than just climate, with the UN outlining 17 Sustainable Development Goals in 2015. In light of this business landscape, this study aims to assess how the Food and Drink industry can become more sustainable through market shaping efforts of microbusinesses. Being closer to their customers and more flexible than large firms, microbusinesses are able to make quick changes. Unfortunately, due to their size, microbusinesses often find their voices going unheard. Therefore, the study has one big objective: to develop sustainability and ethics related metrics that can guide 1) microbusinesses to shape their market and 2) microbusiness funders to identify suitable recipients for their support and funding. These metrics are based on existing actions undertaken by microbusinesses to develop and maintain sustainable business goals. The research aims were derived through a thorough study of existing literature and primary research was conducted through semi-structured interviews. The findings of the research have been split into four themes: meanings of and motivation behind sustainability, sustainable actions of microbusinesses, the support microbusinesses need vs. what they have, and mass consumerism vs. sustainability institutionalisation. These four themes are discussed in light of the literature review and the study concludes that there are certain actions microbusinesses can take to shape markets, such as sourcing local and ethical produce, reducing waste, using environmentally friendly packaging, collaborating and educating the community they operate in. Another conclusion drawn by the study is that microbusinesses, as capable as they are of shaping markets, need support from industry and regulatory bodies. Microbusinesses are not as financially strong as large manufacturing firms, have operational priorities to cater to, and do not always have the time and resources to proactively collaborate to make sustainable change. Therefore, industry and regulatory bodies can support not only through the provision of grants and guidance, but also through sourcing from local businesses for big tenders, showcasing microbusiness work, filling information gaps in the market, and even working as a coordinator to bring microbusinesses together. Lastly, the study also concludes that mass consumerism and sustainability may not be able to coexist, and that making sustainability 'default' in a large industry may require the creation of independent retailers and supermarkets as opposed to giant firms.